Pengukuran Kualitas Pelayanan Polsek Simpang Empat Terhadap Kepuasan Masyarakat Dengan Metode SAW - Sri Helena Utami Saragih; William Ramdhan; Akmal (Jurnal Algoritma, 2026)
Public service is a key indicator in assessing the performance of government agencies, including the police. The Simpang Empat Police Station, as a technical police unit at the subdistrict level, plays a strategic role in providing services to the community. However, there are still complaints regarding long wait times, unfriendly officers, and suboptimal facilities. This study aims to evaluate the quality of public service at the Simpang Empat Police Station using the Simple Additive Weighting (SAW) method. The assessment was based on six criteria: service accuracy, officer attitude and behavior, service speed, clarity of information, transparency of the service process, and communication with the public. Data was collected through a questionnaire administered to service users. The results indicate that Mediation Services (A07) received the highest preference score of 0.9865, followed by Security and Order Services (A02) at 0.9792 and Guidance and Counseling Services (A05) at 0.9752. The average SAW score was 0.9706 with a satisfaction level of 97.06%, which falls into the “very satisfactory” category, indicating that the SAW method is effective for evaluating the quality of public services.